25 years of research on global asphyxia in the immature rat brain. (April 2017) - Barkhuizen, M.; van den Hove, D.L.A.; Vles, J.S.H.; Steinbusch, H.W.M.; Kramer, B.W.; Gavilanes, A.W.D.
Graphical abstract: Adapted fromSparnaaij et al. (2016) . Highlights: Hypoxic ischemic encephalopathy is a common cause of long-term neurological deficits. Only supportive care is available for preterm infants with asphyxia. We describe a translational rat model of global birth asphyxia in very preterm infants. Induced by submersion of uterine horns containing pups and delayed C-section at P0. The degree of locomotor, cognitive and anxiety behavioural deficits depend on asphyxia duration. Abstract: Hypoxic-ischemic encephalopathy remains a common cause of brain damage in neonates. Preterm infants have additional complications, as prematurity by itself increases the risk of encephalopathy. Currently, therapy for this subset of asphyxiated infants is limited to supportive care. There is an urgent need for therapies in preterm infants – and for representative animal models for preclinical drug development. In 1991, a novel rodent model of global asphyxia in the preterm infant was developed in Sweden. This method was based on the induction of asphyxia during the birth processes itself by submerging pups, still in the uterine horns, in a water bath followed by C-section. This insult occurs at a time-point when the rodent brain maturity resembles the brain of a 22–32 week old human fetus. This model has developed over the past 25 years as an established model of perinatal global asphyxia in the early preterm brain. Here we summarize the knowledge gained on the short- and long-term neuropathological and behavioral effects of asphyxia on the immature central nervous system.